NEUROCRYPTOCOCOSIS: : A DISEASE THAT DOES NOT OPEN SPACE FOR NEGLIGENCE IN HIV POSITIVE PATIENTS - Thaine Teodoro, Danielly; Cerqueira Simões Braudes, Isadora; Emanuel Mendes da Silva Santos, Arlys; Ferreira Firmino, Fernanda; Maria Senhorinha, Gláucia; Sena de Lucena, Larissa (Health and Society, 2021)
INTRODUCTION Composed of about 30 species, the genus Cryptococcus has two species of greater clinical relevance in humans, C. neoformans and C.gattii. The first one was not considered a high morbidity species, initially, but in the 1980s, with the institution of the human immunodeficiency virus (HIV), this scenario changed. Since then it has come to be considered the most life-threatening ringworm for patients living with HIV, accounting for about 625,000 deaths annually. OBJECTIVE To determine the main points of neurocriptococcosis in the population with HIV. METHODOLOGY The search for the articles was carried out in the MEDLINE/ PUBMED and BVS databases. The descriptors used were chosen on the BIREME platform in Portuguese and English, and were respectively: Meningitis, Cryptococcal; Acquired Immunodeficiency Syndrome; Diagnosis; Therapeutics; Signs and Symptoms. Other texts were chosen during the course of reading the articles in the databases, according to the bibliographic references. In total, 35 articles were selected to compose this narrative review. DEVELOPMENT Cryptococcosis is more prevalent in urban areas of countries with tropical and subtropical climates. The fungus in question is found in pigeon droppings and the infection occurs by inhalation. Such yeast has tropism for the central nervous system due mainly to ineffective immunity. High morbidity, above all, occurs in patients with a TCD4 cell count below 100/mL, seen in HIV-positive patients. FINAL CONSIDERATIONS Cryptococcosis is the pathology with the highest prevalence in the population with HIV and the one that confers the highest morbidity in this group. It reveals a plural clinic, with neurocriptococcosis being the first opportunistic manifestation in this group. Mortality rates are high and uneven between developed and underdeveloped countries, including those directly related to the choice of initial therapy.